ANALYSIS OF FIELD STRUCTURE AND JUSTIFICATION OF VOLTAGES OF DIAGNOSTICS BY PARTIAL DISCHARGES OF SHIELDED TWISTED PAIRS INSULATION - A.V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2014)
An analysis of the electrostatic field of a cable twisted shielded pair for various types of test voltage: symmetric bipolar, unipolar and asymmetric is carried out. Voltage selection affects the location of the most probable place of arising of the partial discharges, phase characteristics of which are used for technical diagnostics of insulation.